ANALISIS EFISIENSI DAN KEAMANAN KONFIGURASI WEB PROXY DALAM MENGELOLA TRAFIK INTERNET DI LINGKUNGAN PENDIDIKAN - Dadan Rahmat; Zahara Muharraran; M Abil Agustian (INFOTECH journal, 2024)
Internet use in educational settings is increasing, but can cause problems such as access to inappropriate content, the spread of malware, and misuse of bandwidth. Web proxies can be a solution for managing internet traffic efficiently and safely. This article analyzes the efficiency and security of web proxy configurations in managing internet traffic in educational environments. The efficiency of web proxy configuration is influenced by the type of web proxy, cache configuration, and bandwidth configuration. The security of a web proxy configuration is affected by authentication, content filtration, and software updates. Proper web proxy configuration can increase the efficiency and security of internet access for users in educational environments.